Posterior cranial fossa volume in patients with rickets: insights into the increased occurrence of Chiari I malformation in metabolic bone disease - Tubbs, R Shane; Webb, Daniel; Abdullatif, Hussein; Conklin, Michael; Doyle, Scott; Oakes, W Jerry (Neurosurgery, 2004)
Some have proposed that the calvarial thickening seen in patients with rickets results in an increased rate of Chiari I malformation (CIM) in these patients. The present study measures the posterior fossa volume in children with rickets to verify previous case reports indicting a small posterior fossa as the cause for an increased rate of CIM in children with rickets. Patients were chosen by use of a computer database to search for individuals diagnosed with rickets. Nineteen patients were identified with this diagnosis. Seven patients were found from this cohort to have imaging of the head. Axial computed tomographic and magnetic resonance images were analyzed by use of the Cavalieri method to define posterior fossa volumes. These data were then compared with those from age-matched control subjects. Mean volumes of the posterior fossa were significantly reduced in all patients compared with age-matched control subjects (P < 0.0001). We have found that the volume of the posterior fossa is significantly smaller in children with rickets versus age-matched control subjects. Furthermore, 29% of our study group had an associated CIM. We may hope that these data will aid in the further understanding of the pathophysiology of CIM in cases of metabolic bone disease.